1996
DOI: 10.1002/(sici)1098-2337(1996)22:6<437::aid-ab4>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral tactics control the energy costs of aggression: The example of Macropodus opercularis

Abstract: Previous experiments on Betta splendens have shown that energy expenditures related to aggression are under social control. The present paper examines the biochemical energetics of social cohabitation in groups of Macropodus opercularis. The species is closely related to Betta splendens, however, dominants use somewhat different behavioral tactics against intruders. In contrast to Bettas, submissive Macropoduses are not harassed by dominants, but are confined to the bottom of the tank. This results in a reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Contestants must mobilise energy stores to maintain high activity levels during a fight, and this often is reflected as depleted glycogen reserves and increased blood glucose levels (e.g. Haller et al 1996;Campbell et al 2005). To fuel metabolic processes and generate energy, fighters also increase rates of oxygen consumption (Ros et al 2006) and, if the contest escalates persistently, they turn to anaerobic metabolism.…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Contestants must mobilise energy stores to maintain high activity levels during a fight, and this often is reflected as depleted glycogen reserves and increased blood glucose levels (e.g. Haller et al 1996;Campbell et al 2005). To fuel metabolic processes and generate energy, fighters also increase rates of oxygen consumption (Ros et al 2006) and, if the contest escalates persistently, they turn to anaerobic metabolism.…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Paradise fish with their complex behavioral repertoire [ 3 , 5 , 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] are a promising future model organism for behavioral genetics. However, in order to turn them into a modern model organism, it is essential to establish standardized protocols for housing and husbandry [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This unique set of behaviors make the labyrinth fish ideally suited for a range of studies. Indeed, not so long ago, the paradise fish was a popular model for ethologists, and was studied for different aspects of its behavioral repertoire [ 3 , 5 , 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. With the advent of novel molecular techniques, however, other, more established laboratory species (mainly zebrafish ( Danio rerio ) and medaka ( Oryzias latipes )), replaced paradise fish in the realm of behavioral studies as well.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the female‐biased sex ratio could have been caused by higher mortality of males. Both territorial and non‐territorial male R. amarus compete aggressively for mating opportunities (Reichard et al , 2004), which is likely to be costly (Haller et al , 1996; Candolin & Reynolds, 2002; Vollestad & Quinn, 2003), and higher testosterone levels in males at this time compromise immunity (Saino et al , 1995; Casto et al , 2001). In contrast, females spend most time feeding (Reichard et al , 2004).…”
Section: Discussionmentioning
confidence: 99%